Development of a Novel Perfusable Solution for ex vivo Preservation: Towards Photosynthetic Oxygenation for Organ Transplantation - Veloso-Giménez, Valentina; Escamilla, Rosalba; Necuñir, David; Corrales-Orovio, Rocío; Riveros, Sergio; Marino, Carlo; Ehrenfeld, Carolina; Guzmán, Christian Dani; Boric, Mauricio P.; Rebolledo, Rolando; Egaña, José Tomás (Frontiers in Bioengineering and Biotechnology, 2021)
Oxygen is the key molecule for aerobic metabolism but none of the cells in the body can produce it, creating an extreme dependency on external supply. In contrast, several cells in nature can generate oxygen through photosynthesis. As hypoxia is one of the main issues in organ transplantation, specially during preservation, the main goal of this work was to develop the first generation of perfusable photosynthetic solutions, exploring its feasibility for ex vivo organ preservation. Here, the microalgae Chlamydomonas reinhardtii was incorporated in a standard preservation solution, and key aspects such as alterations in cell size, oxygen production and survival were verified. Moreover, osmolarity and rheological features of the photosynthetic solution were comparable to blood. In terms of functionality, the photosynthetic solution proved to be biocompatible and to provide sufficient oxygen to support the metabolic requirement of zebrafish larvae and rat kidney slices. Thereafter, isolated porcine kidneys were perfused, and microalgae reached all renal microvessels. After perfusion and flushing, no signs of tissue damage were detected, and recovered microalgae survived the process. Altogether, this work proposes the use of photosynthetic microorganisms as vascular oxygen factories to generate and deliver oxygen in isolated organs, representing a novel and promising strategy for organ preservation.